ANALISIS KESEHATAN DAN KESELAMATAN KERJA (K3) DENGAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) - Choirul Anwar; Willy Tambunan; Suwardana Gunawan (President University, 2019)
In the current industrial era a lot of progress from machine technology or methods used by companies in their production systems. So that the system of production and productivity in the company takes place effectively, safely, and efficiently. One way to achieve this is by paying attention to the occupational health and safety (K3) of the employees in the company. The identification of work accidents used in this study uses the Hazard and Operability Study (HAZOP) method. In the work system in the PDAM there is work that is vulnerable to work accidents such as in the field of maintenance or maintenance on machinery, water treatment production systems, and work carried out in the workshop. From the results of field observations at the PDAM Tirta Kencana workshop and interviews with workers, there were 50 potential hazards that existed at the PDAM Tirta Kencana workshop and were then classified according to the type of sources into 12 sources of hazards. There are 3 levels of work accident risk from hazard sources obtained from the risk matrix assessment, which has the potential to cause work accidents. The level of risk is an extreme risk of 1 source of hazard, a high risk of 5 sources of hazard, and a moderate risk of 6 sources of hazard. The proposal of the results of this study is to conduct OSH training, conduct work supervision, and perform maintenance on machinery and equipment.